A study of the outcomes of an international baccalaureate diploma program education - Hixon, Cori, author; Cooner, Donna, advisor; Frederiksen, Heidi, committee member; Coke, Pam, committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2017)
The International Baccalaureate Diploma Program is noted by universities and researchers as one of high academic rigor and standards (Culross & Tarver, 2011; Taylor & Porath, 2006); however, students enrolled in IBDPs often cite high levels of perceived stress and lack of social interaction as a result of the rigor (Shaunessy & Suldo, 2010). Anecdotally, parents and educators question the value of an IB education if it puts the mental and social well-being of the child at risk, and yet, there is research supporting the claim that participation in an IBDP prepares students with the knowledge and academic and non-academic skills required to be successful in post-secondary pursuits including university or work force readiness (Bergeron, 2015; Conley, 2008, 2010). Thus, this study addresses the problem between the benefits and risks of an IB education by examining alumni perceptions of the role of the DP in preparing them for post-secondary pursuits. Surveying 20 alumni from the graduating classes of 2006-2014 at Poudre High School in Fort Collins, CO, provided data to examine the outcomes of participation in the IBDP and to measure the quality and effectiveness of the PHS program. The results of this study will provide information for the existing IBDP at PHS to refine, revise, and develop the program with the goal of increasing student enrollment by providing information on the outcomes of an IB education to incoming students and families. A phenomenological approach was taken with this qualitative study because it explored the reflections and lived experiences of participants. Participants' lived experiences in the PHS IBDP and their perceptions of how those experiences impacted their post-secondary pursuits helped to explain what the experience of IBDP was like. The descriptions of alumni experiences and the ways in which those experiences informed other aspects of their life, shed light on the essence of the program itself and the outcomes of participation in that program. Analysis of the data revealed a) participants felt well prepared for post-secondary pursuits, b) influence of the core components was significant but not direct, c) participants felt that overall the program was of value with long term benefits, and d) high levels of stress discussed in the literature were not a major concern for participants in this study. This study was limited by the fact that it was one site in a middle class school district with a consistently high diploma pass rate. Additionally, the DP is housed within the larger comprehensive high school creating a cohort of like-minded learners.
Keywords: diploma program; outcomes; international baccalaureate; alumni study